(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, recommendations on the organization of cost budgeting in economic entities and the evaluation of the effectiveness of resource use in cost control have been developed. The positive aspects of the organization of management accounting in economic entities, effective ways of cost control are detailed. In addition, relevant scientific proposals and practical recommendations have been developed regarding certain problems identified in the field.